Mycoplasma genitalium Compared to Chlamydia, Gonorrhea and Trichomonas as an Etiologic Agent of Urethritis in Men Attending STD Clinics - Gaydos, Charlotte (2009)
OBJECTIVES: This purpose of this study was to investigate prevalence of M. genitalium C. trachomatis, N. gonorrhoeae, and T. vaginalis in men, frequency of coinfections, and relationships among organisms with urethritis in men. METHODS: This was a cross-sectional study of 290 men (age range 19-34 yr) attending Baltimore City STD Clinics. M. genitalium, C. trachomatis, N. gonorrhoeae, and T. vaginalis, during 2004 were detected using nucleic acid amplification tests (NAATs). (N = 153 with urethritis and 137 without urethritis). Demographic characteristics and risk factors were ascertained. RESULTS: The overall prevalences of infection with C. trachomatis, N. gonorrhoeae, T. vaginalis, and M. genitalium, were 20.3%, 12.8%, 3.4%, and 15.2% respectively. Prevalences in men with urethritis were 32.7%, 24.2%, 5.2%, and 22.2% for C. trachomatis, N. gonorrhoeae, T. vaginalis, and M. genitalium, respectively. Percentages of coinfections were high. All men with N. gonorrhoeae had urethritis. C. trachomatis and M. genitalium were found to be significantly associated with urethritis in univariate analysis and in multiple logistic regression analysis. CONCLUSION: The association of M. genitalium with urethritis in this study provides confirmation of the importance of screening men for M. genitalium as a cause of non-gonococcal urethritis and supports treatment considerations for urethritis for agents other than gonococci and chlamydia. SHORT SUMMARY: Men attending STD clinics were found to have high prevalences of M. genitalium (MG), C. trachomatis (CT), and N. gonorrhoeae (NG); moderate prevalence of T. vaginalis. MG was associated with urethritis in addition to NG and CT.